Self‐compassion and hope in the context of body image disturbance and distress in breast cancer survivors. Issue 10 (14th August 2019) - Todorov, Natasha; Sherman, Kerry A.; Kilby, Christopher J.
Abstract: Objective: Greater hope and self‐compassion have individually been associated with lower psychological distress in women with breast cancer. Self‐compassion is also associated with lower body image distress in this population, yet it is unknown whether hope also has this association. This study aimed to investigate the extent to which hope accounts for body image distress and psychological distress in breast cancer survivors alone, and in direct comparison to self‐compassion. Method: A total of 195 women were recruited from the Breast Cancer Network Australia and completed a cross‐sectional online anonymous questionnaire containing self‐report measures of body image (Body Image Scale), self‐compassion (Self Compassion Scale‐SF), hope (State Hope Scale), psychological distress (depression, anxiety, stress; DASS), and demographic/medical questions. Results: Self‐compassion and hope were inversely correlated with all outcomes. Hierarchical linear regression analyses indicated that self‐compassion and hope uniquely explained variance in all outcomes with different magnitudes of strength. Comparison of standardised betas indicated (a) Body image distress—self‐compassion ( B std = −.355) vs hope ( B std = −.161); (b) Stress—self‐compassion ( B std = −.562) vs hope ( B std = −.287); (c) Depression—hope ( B std = −.447) vs self‐compassion ( B std = −.374); (d) Anxiety—hope ( B std = −.406) vs self‐compassion ( B std = −.249). Conclusion: The unique contribution of self‐compassion and hope in explaining body image distress and psychological distress suggests that combined, hope‐focused components of therapy may be suitable additions to the growing array of self‐compassion–based psychosocial interventions to address body image and psychological distress concerns of women with breast cancer.